2015
DOI: 10.1248/bpb.b14-00631
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Rapamycin on Inflammation and Capillary Degeneration in a Rat Model of NMDA-Induced Retinal Injury

Abstract: Inhibitors of the mammalian target of rapamycin (mTOR) have been shown to protect against neuronal injury, but the mechanisms underlying this effect are not fully understood. The present study aimed to examine the effects of rapamycin, an inhibitor of the mTOR pathway, on inflammation and capillary degeneration in a rat model of N-methyl-D-aspartate (NMDA)-induced retinal neurotoxicity. Inflammation and capillary degeneration were evaluated by counting the numbers of CD45-positive leukocytes and Iba1-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…34) Previous studies showed that the suppressive effect of rapamycin on inflammatory responses, such as infiltration of leukocytes and activation of microglia, might prevent secondary retinal damage. 13) Similarly, in the present study, we found that co-injection of everolimus with NMDA prevented increases in CD45-positive cells and Iba1-positive cells and the morphologic transformation of Iba1-positive cells from the ramified form to an amoeboid shape 24 h after NMDA injection. The reduction of inflammatory responses by everolimus may contribute to the prevention of additional retinal damage.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…34) Previous studies showed that the suppressive effect of rapamycin on inflammatory responses, such as infiltration of leukocytes and activation of microglia, might prevent secondary retinal damage. 13) Similarly, in the present study, we found that co-injection of everolimus with NMDA prevented increases in CD45-positive cells and Iba1-positive cells and the morphologic transformation of Iba1-positive cells from the ramified form to an amoeboid shape 24 h after NMDA injection. The reduction of inflammatory responses by everolimus may contribute to the prevention of additional retinal damage.…”
Section: Discussionsupporting
confidence: 87%
“…13,22) The numbers of CD45-positive cells and Iba1-positve cells were counted 24 h after intravitreal injection of vehicle (n=8), NMDA (n=4) or NMDA+everolimus (n=5).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations